A flood wave disaster recovery model for under construction dam projects: findings from Greece. (2016) - Anthopoulos, Leonidas
Dam design and construction teams respect flood wave risks, they perform estimations and define response plans for the project post-completion period. To this end, dams are designed strongly enough to overcome such a disaster. The aim of this paper is to investigate whether a flood wave danger exists during the pre-completion period of a dam project and how a project manager can respond on the occurrence of such a crisis event. In order to answer both these questions, a panel of Greek experts justify this risk and validate a corresponding disaster-recovery model. This model was extracted from literature findings and aligns to international project management standards.